On ?vm(f)-statistical convergence of order ? - Et, Mikail; Gidemen, Hatice (Taylor & Francis Inc, 2020)
In this article we introduce and examine the concepts of statistical convergence of order alpha and strong Cesaro summability of order and give some relations between statistical convergence of order alpha and strong Cesaro summability of order alpha.
Keywords: Statistical convergence; difference sequence